Factors affecting the job quality of agricultural plantation and non-plantation labour the case of cavendish banana in Sto. Tomas Davao del Norte and rice in North Cotabato - Demapanag, Inayah Thea (2016)
The agricultural sector plays an important role in the sustainability and growth of a country. According to the Department of Labor and Employment, a total of 39.8% of the Labour force in the Philippines is employed within this sector specifically those households living in rural areas. The agricultural industry grows and produces two kinds of fruits and crops these are the plantation and non-plantation agricultural crops. Since there are numerous kinds of plantation and non-plantation crops, this study chooses to only focus on Cavendish Banana and Rice sectors of region XI specifically in Sto. Tomas Davao del Norte for Banana and North Cotabato of Rice. And aims to analyze the factors that affect the quality of jobs of agricultural workers: the case of Cavendish banana workers in Sto. Tomas and Rice farmers in Tagum. This research study used a secondary survey data from the study conducted by World Bank entitled Rural Connectivity and Agricultural Supply Chain Analysis in Mindanao, Philippines (2012) as well as data's from Cavendish Banana Jobs Value Chain Analysis (2016) and Rice Jobs Value Chain Analysis (2016). There were a total of 185 grower respondents surveyed for the Cavendish banana industry and 115 farmer respondents for the rice industry of North Cotabato. Both qualitative and quantitative methods were applied to fulfil the objectives of this research study; the qualitative method will be chain analysis on the types of growers operating in Sto. Tomas and rice farmers in North Cotabato based on the job quality indicators identified by the researcher which were wage and benefits, profit and returns to labor. Evaluation and analysis was also made on the several production activities involving the chains of Cavendish banana an 1d rice based on the wage that the workers receive in performing each of the production activities. On the other hand, the quantitative method used in this study is multiple regression which is done through the use of Gnu-Regression Econometrics Time Series Library (GRETL) software. The results chain analysis showed that the plantation industry of the agricultural sector is more profitable than non-plantation industry. And that it is better for growers especially the independent banana growers to be under contractual arrangements with multinational companies. Multinational companies will be able to provide grower with a stable profit and market source as well as access to inputs and machineries to better the quality of their produce. While for the rice industry, it is better for farmers to be under a cooperative most especially for small-scale farmers with no stable market. Being part of the cooperative will give farmers access to credit and input as well as training programs and seminars that will enhance their skill and knowledge on farming. On the other hand, the results of the doing the quantitative method of regression through Gretl showed the relationship between the independent variables (wage, profit, and returns to labor) to the dependent variables ((productivity) of workers and farmers. Based on the regression result of the Cavendish banana industry showed that for every peso increase in the wage of a worker the boxes they produced per hectare increases by 5 units. This exhibits a significant relationship between a worker's wage and his or her productivity while profit only exhibits a minimal effect on a worker's productivity since these worker's are more concerned wage than the profit that is earned by their grower-employer. While the results of regression on rice show that there is a significant relationship between a farmer's profit and productivity which means that the greater the yield and the higher the profit a farmer receives, the more productivity they become. Based on the results of the study, the researcher recommends that the independent farmers to improve the quality of their produce in order to gain market power over the price of their product, growers to engage in contractual arrangements with multicultural companies, employers to provide their workers the exact wage and proper benefits they should receive to increase the quality of their job, avoidance in acquiring loans and credits and most especially both farmers and growers must learn to reduce the cost of their inputs. Aside from this, growers must learn to limit the number of their hired workers and should train their workers to do other jobs in the production process by doing this, the grower will be able to reduce their labour cost and at the same time increase the wage received by the worker. The researcher also strongly recommends fro grower and farmers to be members of cooperatives.